Education on the Preparation of Supplementary Feeding (PMT) Using Local Foods for Undernourished Toddlers at the Asoka 8 Posyandu in Lubuk Linggau - Tasya Diajeng Ayu; Nurwijayanti Nurwijayanti; Harmonedi Harmonedi (CV. Publikasi Indonesia, 2026)
Undernutrition among toddlers remains a significant public health challenge that can negatively affect children's growth, cognitive development, immunity, and future productivity. One strategy to address this issue is the provision of Supplementary Feeding (Pemberian Makanan Tambahan/PMT) based on locally available food ingredients, which can improve nutritional intake while encouraging family independence in preparing nutritious meals. This community service activity aimed to increase the knowledge and skills of mothers of undernourished toddlers regarding the preparation of local food-based PMT at Posyandu Asoka 8, Lubuk Linggau. The activity was conducted using an educational approach involving interactive lectures, leaflet-based nutrition education, discussions, and question-and-answer sessions. The participants consisted of 13 mothers of undernourished toddlers in the working area of Megang Health Center. Evaluation was carried out by assessing participants' understanding before and after the educational intervention through question-and-answer activities and observation of participation during the session. The results showed that prior to education, several mothers had limited knowledge regarding the concept, purpose, nutritional composition, and appropriate preparation methods of local PMT. After receiving education through leaflets and interactive discussions, participants demonstrated improved understanding of PMT preparation, including selecting nutritious local ingredients, determining appropriate portions, and applying proper food processing techniques. This activity indicates that local food-based PMT education is an effective approach to improving maternal knowledge and supporting sustainable nutritional practices for undernourished toddlers. Continuous nutrition education integrated into routine Posyandu activities is recommended to strengthen mothers' capacity in preventing and reducing toddler malnutrition.